SISTEM PENGONTROLAN MI3F DENGAN TIGA KECEPATAN BERBASIS PLC - Suryani Suryani (VERTEX ELEKTRO, 2020)
this final duty have been done [by] system development of Pengontrolan speed of Motor Induce Three Phase use pengontrolan conduct resistor base on PLC. System the controlled [is] speed of Motor Induce Three Phase [pass/through] resistor kontroler by using kontaktor kordinasi with resistor. Arrangement of torque [at] Motor Induction will be more easy to and way of this have been developed [by] [in] some weakness literature,namun of Motor Induce [is] unable to maintain its speed constantly if/when happened change of and also speed of torsi burden. Hence to get constant speed and also improve;repair Motor Induction performance made [by] method of kordinasi kontaktor with resistor that is a[n method arrangement of torsi [at] Motor of Induksi.Penelitian this aim to to  Design system of Pengontrolan MI3F With Three Speed. Object Research in the form of appliance for the scheme of system pengentrolan of Motor Induce Three Phase by 3 speed being based on PLC. Scheme of system pengontrolan of MI3F base on this PLC give method three kcepaatan with aim to for the efektifitas of usage of motor with model three speed. Induction motor can be arranged [by] its speed with three phase that is 500 , 1000, and 1500 rpm.